Study of The Application of Construction Waste Management Strategies in The City of Baghdad - Abdullah A. Alhashemy; Ali H. Hameed; Hatim A. Rashid (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the effectiveness of construction waste management strategies employed by the Baghdad Municipality Department, with a focus on the spatial distribution of waste treatment facilities. Employing ArcMap 10.8, a geospatial analysis was conducted to evaluate the distribution and accessibility of these facilities within the city. Data on waste treatment site locations were gathered through interviews and Google Earth, and subsequently analyzed using network analysis in ArcMap. The findings reveal a significant deficiency in Baghdad's construction waste management system, predominantly relying on recycling and disposal, while neglecting other crucial strategies like reduction, treatment, and recovery. This insufficiency is further exacerbated by the limited number and uneven distribution of treatment plants, leading to indiscriminate waste accumulation and economic losses. The study suggests the urgent need for comprehensive government regulations on waste management, including waste sorting, transportation, and penalties for non-compliance. Additionally, it recommends expanding and evenly distributing waste treatment facilities across Baghdad to optimize waste management efficiency. This study not only highlights the critical gaps in Baghdad's waste management system but also offers a methodological framework for other cities facing similar challenges, emphasizing the role of geospatial analysis in enhancing urban waste management strategies. Highlights : The study identifies major deficiencies in Baghdad's construction waste management, primarily in recycling and disposal practices. Geospatial analysis using ArcMap 10.8 reveals the need for more evenly distributed waste treatment facilities in the city. Recommendations include implementing stringent government regulations and expanding the city's waste management infrastructure. Keywords : Baghdad, Construction Waste Management, Geospatial Analysis, ArcMap, Waste Treatment Facilities